Winners and Losers in Russia's Economic Transition - Brainerd, Elizabeth (American Economic Review, 1998)
The transition to a market economy has produced a substantial and rapid change in the wage structure in Russia. Household surveys taken before and after the transition indicate that overall wage inequality nearly doubled from 1991 to 1994 and has reached a level higher than that in the United States. Returns to both measured skills (education, occupation) and unmeasured skills within groups have increased considerably. Skill premiums across experience groups, however, have become more compressed and relative wages of older workers have declined. In addition, female wages have declined relative to male wages across all percentiles of the wage distribution. Copyright 1998 by American Economic Association.